Maine’s Wind Resource: A Source of Energy and Economic Engine - Parker, Jackson (Maine Policy Review, 2008)
If Maine is to reduce its reliance on fossil fuels, and the associated greenhouse gas emissions, it is important to develop both new sources of energy and new technologies to better access existing sources. Large scale wind power generation is already in operation in a few places in the state, with many new projects in various stages of planning and implementation.